Women’s Access to Higher Education in Indigenous Communities - Yuliatin, Yuliatin; Lalu Sumardi; Mabrur Haslan; Muhammad Zubair (Komunitas: International Journal of Indonesian Society and Culture, 2025)
The research conducted aims to analyze women’s access in indigenous communities to obtain the right to higher education and various factors that influence it. The research subjects were women in the Sade Traditional Village who continued their education to university, and also those who had graduated from high school or equivalent but did not continue to university. The research informants were the parents of the research subjects and traditional leaders in the Sade Traditional Village. Data were collected using interviews, observation, and documentation techniques. Data analysis employed Miles & Huberman’s interactive data analysis, which involves four main steps: data collection, data reduction, presentation, and drawing conclusions or verification. The results of the study show that: (1) women in the indigenous community in the Sade Traditional Village actually have access to fulfilling the right to higher education, as long as they fulfill the provisions/basic principles that are considered good by the local community, namely: (a) maintaining the noble values placed on women, (b) having a commitment to complete education well, (c) ensuring that they can work sustainably in an affordable place without having to live separately from their family, especially their husband, (d) choosing a major/study program that can be directly felt by the local community, (2) there are various factors that influence women’s access in the Sade Traditional Village in obtaining the right to higher education, namely: (1) customary rules, (2) community perceptions about higher education for women, (3) an attitude of resignation to fate, (4) an attitude of not easily believing in new things, (5) self-motivation, (6) accessibility of higher education, (7) parent’s education level, and (8) parent’s economy.